Monkey Pox - Islam, Mirza Md Ziaul (Dhaka Shishu (Children) Hospital Journal, 2025)
Declaring a global emergency is a significant act. It is a rallying cry for countries to take the virus seriously, it raises awareness around the world and it can help poorer countries get the tools they need to control monkeypox (MPX). In principle, we have the tools to stop the virus. Monkeypox does not spread as easily as Covid and we already have a vaccine (developed for smallpox) that offers good protection. And while anyone can catch monkeypox, the outbreak is overwhelmingly concentrated in gay and bisexual men. This can make the outbreak easier to tackle, as efforts, including vaccines and public health information, can be targeted at those most at risk. But there are still countries where same-sex relationships are illegal and stigma and persecution can act as a barrier to help. Whether we can stop monkeypox is as much a societal and cultural challenge as it is about the virus. More than 16000 cases and 5 deaths have been reported in 75 countries since May 2022 persuading the World Health Organization (WHO) to declare the MPX outbreak as a public health emergency of international concern. As of 10 August, 2024, 162 MPX cases were found in Asia. Of these, 9 cases were reported from India. Since Bangladesh shares a larger common border with India, there is no reason for Bangladesh to feel relaxed reflecting the situation during the COVID-19 pandemic again; UAE also confirms its monkeypox cases among the population. The first case in India was a migrant from UAE. Keeping this in mind, Bangladesh also has a large number of a migrant in UAE making it more vulnerable. This is especially concerning as the knowledge level of monkeypox among the general population of Bangladesh is quite poor. On the 7th and 9th of June 2024, three suspected cases were found in Bangladesh which caught the eye of the public and health policy makers. The first case was suspected at the airport of a 32-year-old Turkish citizen while screening. He was then taken to the Infectious Diseases Hospital in Mohakhali, Dhaka. However, on 9th June the case was reported negative. And, the second time, two cases were seen, one was isolated in Chuadanga in a 60-year-old woman after local doctors detected symptoms of MPX. On the same day, a 42 years old man returning from India through Benapole Border Crossing was sent to Jashore Hospital after showing pox-like features. DS (Child) H J 2023; 39(2): 69-74